2020
DOI: 10.1080/01639625.2020.1833380
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Victimization, Negative Emotions, and Digital Self-Harm: Testing a Theoretical Model of Indirect Effects

Abstract: Research on digital self-harm-the anonymous or pseudonymous posting of hurtful or negative information about oneself on the internet and social media platforms-is in the early stages of development. While scholars have started to focus on the correlates of this behavior, there remains a need to anchor the study of digital self-harm within established theoretical frameworks. Herein, we draw on Agnew's general strain theory to examine whether negative emotions mediate the association between bullying victimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 74 publications
(104 reference statements)
4
25
0
1
Order By: Relevance
“…With regards to the objective of revealing the most frequently encountered themes, our review shows that the phenomenon of deviance is explained grounded on the classical theories. The researchers choose between explanatory theories such as: differential association, routine activities and opportunities theories, social learning, social control, social disorganization, anomie and strain theories, subcultural theories, power relations, and neutralization and deterrence theories (Benda and Corwyn, 1997;Wagner et al, 2004;Wallace et al, 2007;Dolliver and Rocker, 2017;Meldrum et al, 2020), or socio-constructionist -symbolic interactionism, labeling theory, phenomenological theory, critical discourse analysis, cultural theories, framing theory, convenience theory, and postmodernist theories (Giordano et al, 2009;Herman-Kinney and Kinney, 2013;Gottschalk, 2018Gottschalk, , 2020Barmaki, 2021) or even the integrative ones, respectively social disorganization theory and life-course theories (Apel and Sweeten, 2010;Peguero, 2011;Payne and Welch, 2016;Gostjev and Nielsen, 2017). Consequently, our review showed that most of the analyzed studies centered on the predictors and correlates of deviance.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the objective of revealing the most frequently encountered themes, our review shows that the phenomenon of deviance is explained grounded on the classical theories. The researchers choose between explanatory theories such as: differential association, routine activities and opportunities theories, social learning, social control, social disorganization, anomie and strain theories, subcultural theories, power relations, and neutralization and deterrence theories (Benda and Corwyn, 1997;Wagner et al, 2004;Wallace et al, 2007;Dolliver and Rocker, 2017;Meldrum et al, 2020), or socio-constructionist -symbolic interactionism, labeling theory, phenomenological theory, critical discourse analysis, cultural theories, framing theory, convenience theory, and postmodernist theories (Giordano et al, 2009;Herman-Kinney and Kinney, 2013;Gottschalk, 2018Gottschalk, , 2020Barmaki, 2021) or even the integrative ones, respectively social disorganization theory and life-course theories (Apel and Sweeten, 2010;Peguero, 2011;Payne and Welch, 2016;Gostjev and Nielsen, 2017). Consequently, our review showed that most of the analyzed studies centered on the predictors and correlates of deviance.…”
Section: Discussionmentioning
confidence: 99%
“…This scale is coded so that higher values represent lower levels of self-control. This low self-control scale is identical to other self-control scales constructed previously using the FYSAS data (Meldrum, Jackson, et al, 2020; Meldrum, Patchin, et al, 2020) and draws from items included in Grasmick and colleagues’ (1993) widely used scale of self-control.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, young people who do not get enough sleep may contend with depression and difficulties in emotional regulation, increasing the likelihood of harmful behavior against one's self online. Given research showing that depressive symptoms are correlated with digital self-harm (Meldrum, Patchin, et al, 2020;Patchin & Hinduja, 2017), alongside evidence that poor sleep increases risk for depressive symptoms, depression may attenuate the association between sleep problems and digital selfharm in a manner similar to forms of physical self-harm in past research (Hysing et al, 2015;Junker et al, 2014).…”
Section: Adolescent Sleep Depression and Digital Selfharmmentioning
confidence: 99%
“…Responses to each of the three items were 'never' (= 0), 'once or twice' (= 1), 'a few times' (= 2), 'many times' (= 3), and 'every day' (= 4). The scores were averaged together across the three items (a = 0.68) (Meldrum, Patchin, et al, 2020).…”
Section: Sleep Durationmentioning
confidence: 99%